2001
DOI: 10.1002/1099-0682(200108)2001:8<2061::aid-ejic2061>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Salt Formed by Mixed-Valence Vanadium(IV, V) [(VO)2O(bpy)2(C2O4)2] Anions and Ferromagnetic [Cu2(bpy)4(C2O4)] Cations: Structure, Spectroscopic Characterization and Magnetic Properties

Abstract: The new heterometallic, mixed-valence compound [Cu 2 (bpy) 4 (C 2 O 4 )][(VO) 2 O(bpy) 2 (C 2 O 4 ) 2 ] 2 ·10H 2 O has been synthesized, its crystal structure determined and its spectroscopic characterization accomplished by means of solid-state vibrational (far and mid FTIR) spectroscopy. The title compound crystallises in the triclinic system, space group P1 (No. 2) [a = 13.488(5) Å , b = 14.160(6) Å , c = 15.829(9) Å , α = 87.22(2)°, β = 66.33(2)°, γ = 64.49(2)°, V = 2471(2) Å 3 , Z = 1]. The compound consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Due to a poor overlap between the axial oxalato oxygen orbital and the metal d italicx 2 italicy 2 orbital, a ferromagnetic coupling dominates the magnetic properties of the Cu dinuclear unit of complex 2 . The magnitude of the coupling observed is in the same range as several reported examples 25,26…”
Section: Resultssupporting
confidence: 81%
“…Due to a poor overlap between the axial oxalato oxygen orbital and the metal d italicx 2 italicy 2 orbital, a ferromagnetic coupling dominates the magnetic properties of the Cu dinuclear unit of complex 2 . The magnitude of the coupling observed is in the same range as several reported examples 25,26…”
Section: Resultssupporting
confidence: 81%
“…Broad absorption at 935 cm –1 is expected for the presence of V=O stretch, which is almost in agreement with [VO(cat) 2 ] 2– (V=O 950 cm –1 ) reported in Cooper’s work 16. It is reported that ν (Cu–N) absorption lies at around 287 cm –1 ,27 which cannot show in the 4000–400cm –1 range.…”
Section: Resultsmentioning
confidence: 99%